2010
DOI: 10.1200/jco.2009.25.0977
|View full text |Cite
|
Sign up to set email alerts
|

Expression Signature of E2F1 and Its Associated Genes Predict Superficial to Invasive Progression of Bladder Tumors

Abstract: We present a molecular signature that can predict, at diagnosis, the likelihood of bladder cancer progression and, possibly, lead to improvements in patient therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
265
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 297 publications
(281 citation statements)
references
References 35 publications
11
265
1
Order By: Relevance
“…Expression was independent of clinical stage, grade or the presence of lymph node metastases. These data confirm the conclusion from our previous global analysis of HDAC isoenzyme expression and in silico analyses of publicly available data sets [32][33][34][35][36] that HDAC6 expression is generally variable in urothelial cancers, but that significant overexpression does occur in individual cases, highlighting HDAC6 as a potential target for cancer therapy. Similarly variable results on HDAC6 expression levels have been published for hepatocellular cancers.…”
Section: Discussionsupporting
confidence: 79%
“…Expression was independent of clinical stage, grade or the presence of lymph node metastases. These data confirm the conclusion from our previous global analysis of HDAC isoenzyme expression and in silico analyses of publicly available data sets [32][33][34][35][36] that HDAC6 expression is generally variable in urothelial cancers, but that significant overexpression does occur in individual cases, highlighting HDAC6 as a potential target for cancer therapy. Similarly variable results on HDAC6 expression levels have been published for hepatocellular cancers.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, immunohistochemical analyses indicated that HES1 expression was significantly lower in the muscle invasive bladder carcinomas (MIBC) compared with that in nonmuscle invasive tumors ( Figure 6C and Supplemental Figure 13). Finally, an independent analysis of Oncomine-deposited data (33)(34)(35) confirmed these clinical findings (Supplemental Figure 14). These observations indicate that low levels of HES1 associate with mesenchymal features and invasive properties in human bladder carcinomas.…”
Section: Notch Pathway Inactivation Promotes Bladder Cancer In Micesupporting
confidence: 64%
“…From these studies, it is apparent that low-grade noninvasive and high-grade muscle-invasive tumors harbor distinct gene expression patterns, and that further molecular subsets can be identified within low-grade and high-grade tumors (5,(11)(12)(13)(14). Moreover, a number of gene signatures have been developed that can predict tumor stage, lymph node metastases, and bladder cancer progression (11)(12)(13)(15)(16)(17)(18). There are established gene expression patterns that differentiate lowgrade and high-grade tumors; however, there are little data identifying intrinsic subtypes specifically within high-grade disease.…”
mentioning
confidence: 99%